2019
DOI: 10.3389/fmicb.2019.00015
|View full text |Cite
|
Sign up to set email alerts
|

The ISApl12 Dimer Circular Intermediate Participates in mcr-1 Transposition

Abstract: Objectives: The mobile colistin resistance gene mcr-1 is a serious threat to global human and animal health. The composite transposon Tn6330 and its circular intermediate were proposed to be involved in the spread of mcr-1 but their roles remain poorly understood.Methods: To further explore the intermediates during the transposition of Tn6330, we engineered Escherichia coli strains that carry an intact Tn6330 transposon or its deletion derivatives. PCR assays were performed to detect IR-IR junctions and possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
(46 reference statements)
5
21
0
Order By: Relevance
“…To confirm the IS CR2 -mediated tet (X) transfer, a transposition assay of tet (X) was conducted as previously reported for mcr-1 [ 32 ]. The putative transposition unit of tet (X3) in Clade_U6 10FS3-1, namely Δ tpnF - tet (X3)-hp-hp-IS CR2 , was cloned in a suicide plasmid pSV03 using the ClonExpress Ultra One Step Cloning Kit (Vazyme, China) (Additional file 1 : Table S1) and then transformed into competent E. coli WM3064.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm the IS CR2 -mediated tet (X) transfer, a transposition assay of tet (X) was conducted as previously reported for mcr-1 [ 32 ]. The putative transposition unit of tet (X3) in Clade_U6 10FS3-1, namely Δ tpnF - tet (X3)-hp-hp-IS CR2 , was cloned in a suicide plasmid pSV03 using the ClonExpress Ultra One Step Cloning Kit (Vazyme, China) (Additional file 1 : Table S1) and then transformed into competent E. coli WM3064.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies illustrate that interactions between physiological characteristics and the intestinal metagenome function of an individual are attributed to bacterial community diversity or some specific bacterial groups, e.g., species or functional clusters [ 28 , 29 ]. Previous studies have suggested associations between intestinal metagenome and environmental fluctuation, for example, the gut microbial community changes with habitat fragmentation and degradation [ 30 , 31 , 32 ], altitude [ 33 , 34 ], season [ 35 ], and climate change [ 36 , 37 ] of locations where the hosts live. Cold acclimated laboratory mice experience a dramatic change in gut microbiota composition as temperature increases [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In brief, we synthesized a cassette in which the mcr-2 and orf genes are flanked by IS Ec69 on both sides and cloned into the vector pUC57, generating the plasmid pUC57- mcr-2 . R6K- Bam HI and R6K- Eco RI primers ( Table 2 ) were used to PCR amplify the backbone using pSV03 ( He et al, 2019 ) as a template which contained the conditional replication origin R6K and Cm R (chloramphenicol) resistance. The amplicon was sub-cloned into the Bam HI and Eco RI restriction sites in pUC57 that contained Tn 7052 to obtain recombinant plasmid pJS05 ( Supplementary Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%
“…The transfer of antimicrobial resistance genes has been found to be catalyzed by specific mobile elements such as insertion element and integron. For instance, IS Apl1 , originally found in Actinobacillus pleuropneumoniae , is located upstream of the mcr-1 gene in the first described mcr-1 -harboring IncI2 type plasmid pHNSHP45 ( Liu et al, 2015 ; Ye et al, 2016 ) and is able to mediate mcr-1 mobilization ( Poirel et al, 2017 ; He et al, 2019 ). Similarly, IS Ec69 , encoding a 217-amino-acid-long DDE-type transposase, belongs to the IS 1595 family and is flanked by two inverted repeats, which share 16/19 nucleotide identity to inverted repeats from the IS 1016C2 transposase.…”
Section: Introductionmentioning
confidence: 99%